2016
DOI: 10.5194/soil-2-287-2016
|View full text |Cite
|
Sign up to set email alerts
|

Climate and soil factors influencing seedling recruitment of plant species used for dryland restoration

Abstract: Abstract. Land degradation affects 10-20 % of drylands globally. Intensive land use and management, largescale disturbances such as extractive operations, and global climate change, have contributed to degradation of these systems worldwide. Restoring these damaged environments is critical to improving ecosystem services and functions, conserve biodiversity, and contribute to climate resilience, food security, and landscape sustainability. Here, we present a case study on plant species of the mining intensive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 85 publications
0
51
0
4
Order By: Relevance
“…En los ambientes forestales, el patrón espacial y temporal de la vegetación dominante tendrá una clara influencia sobre las pérdidas de suelo por erosión hídrica, pues influye de dos maneras: (i) interfiriendo en la energía asociada a los procesos erosivos (Thornes, 1990;Cerdà, 2001); y (ii) modificando las propiedades físico-químicas de los suelos que la albergan (Thornes, 1990;Castillo et al, 1997;Muñoz-Rojas et al, 2016c). Así, durante la estación seca mediterránea, la falta de agua en la matriz del suelo se traduce en una reducción drástica de los inputs de SOC y, por tanto, a largo plazo, en la pérdida de fertilidad de los mismos (Van Wesemael y Veer, 1992;Fons y Vallejo, 1997;Martínez-Murillo et al, 2016a;Muñoz-Rojas et al, 2016a).…”
Section: Introductionunclassified
“…En los ambientes forestales, el patrón espacial y temporal de la vegetación dominante tendrá una clara influencia sobre las pérdidas de suelo por erosión hídrica, pues influye de dos maneras: (i) interfiriendo en la energía asociada a los procesos erosivos (Thornes, 1990;Cerdà, 2001); y (ii) modificando las propiedades físico-químicas de los suelos que la albergan (Thornes, 1990;Castillo et al, 1997;Muñoz-Rojas et al, 2016c). Así, durante la estación seca mediterránea, la falta de agua en la matriz del suelo se traduce en una reducción drástica de los inputs de SOC y, por tanto, a largo plazo, en la pérdida de fertilidad de los mismos (Van Wesemael y Veer, 1992;Fons y Vallejo, 1997;Martínez-Murillo et al, 2016a;Muñoz-Rojas et al, 2016a).…”
Section: Introductionunclassified
“…2). Several studies have shown that inadequate soil water storage is the major limiting factor for the sapling establishment in semiarid areas (Haase and Rose, 1993;Whisenant et al, 1999;South, 2000;HuesoGonzález et al, 2015;Muñoz-Rojas et al, 2016c), and others have reported new techniques needed to increase the AWC in dryland soils (Tongway and Ludwing, 1996;Shachak et al, 1998). Ros et al (2006) showed that the addition of amendments (urban organic waste, green waste, manure, and sewage sludge) favored the development of vegetation cover in Spain because of increased soil moisture.…”
Section: Available Water For Plants and Their Impact On Vegetation Esmentioning
confidence: 99%
“…Vegetation plays a fundamental role in soil conservation (Thornes, 1990;Castillo et al, 1997;Cerdà, 2001;Muñoz-Rojas et al, 2016c). In Mediterranean ecosystems, increasing forest cover has been considered a common technique for mitigating the effects of desertification (Nykvist, 1983;Vallejo et al, 2000;Le Honeuérou, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations